ANALISIS EFEKTIVITAS DAMPAK PENINGKATAN JUMLAH BESARAN PENGHASILAN TIDAK KENA PAJAK TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI PADA KPP PRATAMA MANADO - Weol, Stefi Cristiani; Nangoi, Grace B.; Wangkar, Anneke (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Non-Taxable Income is the minimum living cost to be able to live a decent life. Changes Last Non Taxable Income namely No.101/PMK.010/2016,began to apply on January 1,2016 until present. The purpose of this study is to analyze the effect of their changes Non-Taxable Income on income tax revenue. The analytical method used is descriptive data. The results showed that PTKP changes have a good impact on the growth of the number of taxpayers in each year, but considered not effective against income tax revenue. This shows that the increase of PTKP is not the dominant factor in influencing income tax revenue.Keywords :Non-Taxable Income, Tax Income (PPh) Article 21